The Effect of Academic Supervision and Sustainable Professional Development on the Professional Competence of Junior High School Teachers in North Penajam Paser District - Sohrah, Sitti; Hariyati, Nunuk; Wulandari, Ayu; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Academic Supervision (X1) and Continuous Professional Development (X2) on the Professional Competence of Junior High School Teachers (Y) in Penajam Paser Utara Regency. The research employed a quantitative approach using a survey method. The sample consisted of 234 junior high school teachers selected proportionally from the research population. Data were collected through questionnaires using a Likert scale to measure the variables of Academic Supervision, Continuous Professional Development, and Professional Competence. The collected data were analyzed using multiple linear regression with the assistance of a statistical program. The results indicate that partially Academic Supervision (X1) has a positive and significant effect on Professional Competence (Y) with a significance value of 0.000 (0.05). Continuous Professional Development (X2) also shows a positive and significant effect on Professional Competence (Y) with a significance value of 0.000 (0.05). Simultaneously, Academic Supervision (X1) and Continuous Professional Development (X2) significantly influence Professional Competence (Y), as indicated by an F value of 15.364 with a significance level of 0.000. The coefficient of determination (R Square) of 0.117 indicates that 11.7% of the variance in teachers’ professional competence (Y) can be explained by Academic Supervision (X1) and Continuous Professional Development (X2), while the remaining 88.3% is influenced by other factors outside the research model.